A CRITIQUE OF THE ETHICAL IMPLICATION OF THE EXISTENTIALIST PHILOSOPHY OF MARTIN HEIDEGGER - Kingsley Ugwu, Anayochukwu; Chigozie Ozoemena, Leo (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
This paper sets out to interrogate the ethical implications in the existentialist philosophy of Martin Heidegger as enshrined in his articulation on the ontology of the Dasein and existence. For Heidegger, the question of being starts with the Dasein whose existence stands as the beginning point to holistically grasp reality. Only the Dasein exists while every other being merely is; this is because the existentialia (nature, existence and experience) of the Dasein explains consciousness, freedom, will, etc. Thus, with this existential nature, Dasein becomes the custodian and master of his/her own ethical principles. The problem with such position is that with the extent of freedom accrued to Dasein, there is the possibility of drive to self-ruin, degrading of the existential value of other beings described as merely are, the possibility of anti-social affairs, subjectivity of values, among others. However, the thesis the paper defends is that there are challenges in Heidegger’s existentialist moral principles hence the need to recognize the individuality of the self as pictured in the Dasein and the socialization of selves through experience. The paper shall contribute by analytically pointing out the relevance of the Heideggerian ethical principles in the African life. It shall adopt hermeneutical method in an existentialist design to critically interrogate the Heideggerian ethics.